(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Ensuring food safety and quality is a global priority, yet conventional detection methods often fall short in speed, sensitivity, and adaptability. This review highlights the transformative role of nanotechnology in biosensor development, offering innovative solutions for real-time, high-precision monitoring across the food supply chain. It explores the fundamental components and mechanisms of biosensors, emphasizing how nanomaterials—through enhanced surface reactivity, signal amplification, and structural stability—significantly improve sensitivity, selectivity, and durability. The article categorizes nanobiosensors based on detection mechanisms (electrochemical, optical, and mass-based) and biorecognition strategies (enzymatic, immunochemical, and microbial). Practical applications are discussed, including pathogen detection using metal nanoparticles, toxin and allergen sensing via carbon quantum dots, freshness evaluation through colorimetric nanostructures, and fermentation control using electrochemical nanobiosensors. These advancements underscore the potential of nanobiosensors to revolutionize food safety monitoring and quality assurance.